Hi Oryan.
I'll show you how to solve this with a similar question:
f(x) = 3x^{2}7
g(x) = 5+8x^{1}
Find g(f(1)).
Remember BEDMAS from elementary school? It says do what's in the brackets first, so g(f(1)) becomes first a question of what is f(1)?
Plug it in: f(1) = 3(1)^{2}  7 = 3  7 = 4.
Now replace f(1) with 4: g(f(1)) = g(4). So what is g(4)?
Substitute 4 for x in the expression for g(x):
g(4) = 5 + 8(4)^{1} = 5  8/4 = 3.
There is slightly different approach as well:
in g(x) = 5 + 8x^{1} we are saying that whatever is between the
parentheses on the left hand side replaces x on the right hand side.
This means g(f(x)) = 5+ 8(f(x))^{1}.
But we can substitute for f(x) now on the right hand side:
So g(f(x)) = 5 + 8(3x^{2}7)^{1} = 5 + 8 / (3x^{2}  7).
And now to solve g(f(1)) you can substitute 1 for x:
g(f(1) = 5 + 8 / (3(1)^{2}  7) = 5 + 8 / (3  7) = 5 + 8 / (4) = 3.
Hope this helps,
Stephen La Rocque.
